Fighting methicillin-resistant staphylococcus aureus with targeted nanoparticles - Andrade, Stephanie (2023)
Antimicrobial resistance (AMR) is considered one of the greatest threats to global health. Methicillin-resistant Staphylococcus aureus (MRSA) remains at the core of this threat, accounting for about 90% of S. aureus infections widespread in the community and hospital settings. In recent years, the use of nanoparticles (NPs) has emerged as a promising strategy to treat MRSA infections. NPs can act directly as antibacterial agents via antibiotic-independent activity and/or serve as drug delivery systems (DDSs), releasing loaded antibiotics. Nonetheless, directing NPs to the infection site is fundamental for effective MRSA treatment so that highly concentrated therapeutic agents are delivered to the infection site while directly reducing the toxicity to healthy human cells. This leads to decreased AMR emergence and less disturbance of the individual’s healthy microbiota. Hence, this review compiles and discusses the scientific evidence related to targeted NPs developed for MRSA treatment.